2011
DOI: 10.1007/s10911-011-9232-2
|View full text |Cite
|
Sign up to set email alerts
|

Functional Adaptations of the Transcriptome to Mastitis-Causing Pathogens: The Mammary Gland and Beyond

Abstract: Application of microarrays to the study of intramammary infections in recent years has provided a wealth of fundamental information on the transcriptomics adaptation of tissue/cells to the disease. Due to its heavy toll on productivity and health of the animal, in vivo and in vitro transcriptomics works involving different mastitis-causing pathogens have been conducted on the mammary gland, primarily on livestock species such as cow and sheep, with few studies in non-ruminants. However, the response to an infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 104 publications
4
51
0
Order By: Relevance
“…The SDiff was higher for PI and plasma NEFA for most diseases, especially all diseases (Table 4), and suggests that changes in PI and plasma NEFA are better predictors of disease risk than EBAL, plasma BHBA, and glucose after parturition. Our results show that an index for PI, based on plasma NEFA, BHBA, and glucose, relates to risk for most diseases and supports the growing evidence linking overall metabolic status to risk of infectious Loor et al, 2011;Ingvartsen and Moyes, 2012) and noninfectious diseases (Ingvartsen, 2006;Huzzey et al, 2011) in dairy cows. The study showed that prepartal degree of PI was linked to disease after calving.…”
Section: Metritissupporting
confidence: 85%
See 1 more Smart Citation
“…The SDiff was higher for PI and plasma NEFA for most diseases, especially all diseases (Table 4), and suggests that changes in PI and plasma NEFA are better predictors of disease risk than EBAL, plasma BHBA, and glucose after parturition. Our results show that an index for PI, based on plasma NEFA, BHBA, and glucose, relates to risk for most diseases and supports the growing evidence linking overall metabolic status to risk of infectious Loor et al, 2011;Ingvartsen and Moyes, 2012) and noninfectious diseases (Ingvartsen, 2006;Huzzey et al, 2011) in dairy cows. The study showed that prepartal degree of PI was linked to disease after calving.…”
Section: Metritissupporting
confidence: 85%
“…For decades, researchers have used calculated energy balance (EBAL), primarily based on DMI, milk yield, and milk components, as the gold standard to reflect the degree of change in energy mobilization during early lactation in relation to risk of disease. Studies have shown that calculated negative EBAL, and the metabolites that characterize negative EBAL, are associated with reduced fertility (Walsh et al, 2011), immune function and increased risk of some infectious Loor et al, 2011) and noninfectious diseases (Ingvartsen, 2006;Huzzey et al, 2011). We hypothesize that an index for PI, based on several metabolites in blood, will more directly relate to mechanisms associated with the development of several diseases during early lactation and, in turn, will be a better predictor of risk of disease than, for example, standard methods used to calculate EBAL described previously (National Research Council, 2001;Friggens et al, 2007) or the use of individual metabolites alone.…”
Section: Introductionmentioning
confidence: 99%
“…This innate immune response pathway has been previously reported to be among the most-activated in several studies involving mammary gland bacterial infection [50]. Innate immune response-related pathways including ‘Toll-like receptor’ (File S2), but especially the pathways related to the immune cell migration or activity (e.g., ‘Leukocyte transendothelial migration’, and ‘T cell receptor signaling pathway’), were more induced in OF vs. RE, particularly at +14 d. The DIA analysis of GO BP indicated a larger activation of macrophage in OF vs. RE but, contrary to the KEGG pathway results, indicated a more induced chemotaxis of some of the immune cells in RE vs. OF at +14 d (File S4).…”
Section: Resultsmentioning
confidence: 96%
“…Dairy cows have a moderate, although consistent, increase only for the genes coding for lactoperoxidase and lactoferrin ( Figure 2). Collectively, those data might indicate an overall increase in the innate immune response of the mammary gland during lactation [103] and/or an increase in milk antimicrobial activity in all species during lactation. It appears that the goat, mouse and pig have a higher antimicrobial activity in the milk due to the spike of specific activities (i.e., lactoperoxidase in goat and lactoferrin in monogastric).…”
Section: Figurementioning
confidence: 81%